KONSENTRASI TOTAL SENYAWA ANTOSIANIN EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa L.) : PENGARUH TEMPERATUR DAN pH - Hayati, E.K.; Budi, U.S; Hermawan, R. (Jurnal Kimia (Journal of Chemistry), 2013)
Recently, Roselle ( Hibiscus sabdariffa L.) has been used for tea. Based on this background, research was conducted with the aims: (1) To determine the rate of anthocyanin degradation heating of the roselle calyx extract ( Hibiscus sabdariffa L.), (2) To determine the effects of changes during storage on the stability and total concentration of anthicyanin. This research was conducted by extracting the sample with 2% citric acid. Concentrated extract was used to test the stability upon heating temperature, pH during the storage process for ± 30 days. The results of this study indicate that extracts of roselle calyx ( Hibiscus sabdariffa L.) experienced a decrease in concentration at 80°C. The anthocyanin degradation rate followed the equation of r = 0.014 T – 1.169 with the lowest concentration of 32.916 mg / L.
Keywords: Roselle (Hibiscus sabdariffa L.), anthocyanins, degradation, temperature, pH